1994
DOI: 10.3109/02841869409083946
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer Report of a Series of 50 Cases

Abstract: Fifty consecutive cases of male breast cancer (MBC) treated in a single institution were studied. Presentation of the disease, histology, pattern of relapse, and major prognostic factors were similar to those known in female breast cancer (FBC). Five-year disease-free interval and survival were 59% and 75% respectively. Endocrine therapy for treatment of metastatic MBC was proven to be effective with a response rate of about 50% of patients, unselected with regard to oestrogen receptors. A group of patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…A limited number of prospective, randomized clinical studies exist, which indicate the benefit of adjuvant systemic therapy for MBC (88). On the other hand, decreased recurrence and mortality rates have been reported with adjuvant CT in retrospective studies (53,89). Furthermore, the prognosis and response rates to therapy in with metastatic MBC are similar to those of women.…”
Section: Chemotherapy (Ct)mentioning
confidence: 96%
“…A limited number of prospective, randomized clinical studies exist, which indicate the benefit of adjuvant systemic therapy for MBC (88). On the other hand, decreased recurrence and mortality rates have been reported with adjuvant CT in retrospective studies (53,89). Furthermore, the prognosis and response rates to therapy in with metastatic MBC are similar to those of women.…”
Section: Chemotherapy (Ct)mentioning
confidence: 96%
“…For ductal carcinoma in situ (DCIS), a simple mastectomy where the entire breast is removed, including the nipple, areola, and skin but not all the axilla lymph nodes or lumpectomy followed by adjuvant radiation therapy to the breast is recommended. However, a number of studies have suggested that, although radiation therapy reduces the risk of local recurrence, it has no impact on overall survival (Cutuli et al, 1995;Donegan, Redlich, Lang, & Gall, 1998;Izquierdo, Alonso, De Andres, & Ojeda, 1994;Yidrim & Berberoglu, 1998).…”
mentioning
confidence: 99%
“…At a median follow-up of 52 months, recurrent disease was reported in four (36%) and seven (64%) patients remained disease-free leading the authors to advocate the use of chemotherapy [29]. In another retrospective analysis that evaluated the effect of adjuvant therapy (chemotherapy, hormonal therapy or both), superior disease-free survival was reported in 17 patients who received adjuvant therapy compared with 21 patients that did not receive any form of adjuvant therapy (72% vs. 47%) [30]. The effect of adjuvant therapy was evaluated in a retrospective study of 51 patients treated with hormonal, chemotherapy or both.…”
Section: Discussionmentioning
confidence: 94%
“…Patients who received adjuvant systemic therapy had a 43% lower risk of death compared with patients who had not received any form of adjuvant therapy [31]. While these reports and others suggest the possibility of benefit with the adjuvant chemotherapy, they must be interpreted cautiously in view of small patient numbers, limited follow-up and the heterogeneity in disease stage and adjuvant treatment modality studied [16,[29][30][31].…”
Section: Discussionmentioning
confidence: 97%